Caracterización de los helechos (pterydophytas) presentes en el campus salache de la universidad técnica de Cotopaxi. - Albán Camacho, Mónica Alexandra (2020)
This project aims to characterize the ferns of the Salache campus, to meet our objectives a set of activities were contemplated, such as: assessing the state of knowledge of the Pteridophytas in the Province of Cotopaxi, delimitation of the study area in four areas for facilitate and systematize the sampling and collection of specimens, assembly of samples, identification of specimens using taxonomic keys and elaboration of technical sheets. Among our results we can highlight, the Pteridophytas flora of the Cotopaxi province is made up of 23 families, 73 genus and 360 species, the families with the greatest diversity were Dryopteridaceae (10 genus), Polypodiaceae (19) y Pteridaceae (11), while the genera with more species were Elaphoglossum (47), Asplenium (36). From the inventory of ferns at Salache campus 4 families are reported (Equisetaceae, Pteridaceae, Polypodiaceae, Thelypteridaceae), 7 genus and 7 species (Equisetum bogotenses Kunt, Niphidium longifolium (Cav.) C.V. Morton & Lellinger, Pleopeltis polypodioides (L.) EG Andrews & Windham, Cheilanthes bonariensis (Willd.) Proctor, Myriopteris myriophilla (Desv.) Sm., Pellaea ternifolia (Cav.) Link y Thelypteris caucaensis (Hieron.) Alston, the area with the greatest diversity of species was the upper zone with two families, Pteridaceae with 3 genus and 3 species (Cheilanthes Bonariensis, Myriopteris myriophilla y Pellaea ternifolia); and Polypodiaceae with 2 genus and 2 species (Pleopeltis polypodioides, Niphidium longifolium). While the mountainous and medium zone presented less species diversity (Niphidium longifolium y Thelypteris caucaensis). Additionally, technical data sheets with macro and micrographs of each one of the inventoried species were generated. In this way, we hope that this research will serve as a basic study instrument for students and teachers on the knowledge of the group.